THE EFFECT OF FUNDING DECISION, PROFITABILITY, AND LIQUIDITY IN COMPANY VALUE ON LQ45 MANUFACTURING ISSUERS 2014-2019 - Rosyidah, Salma; Sudjono, Sudjono (Dinasti Publisher, 2021)
The reason for this study is to analyze the effect of funding decisions, profitability and liquidity on firm value in LQ45 manufacturing issuers. Annual data reports of the company from 2014 to 2019 are the data for this study. Sampling of companies using purposive sampling method. From the predetermined criteria, only 8 companies can meet the criteria as research samples. The analytical strategy used in this study is panel data regression analysis and uses the Common Effects model with R2 value of 93.87%. Output of this study to show that fund decision, profitability and liquidity are affecting towards firm value and profitability is the most affecting variable on company value.